Nonepithelial Tumors and Tumor-like Lesions of the Skin and Subcutis in Children. (April 2018) - Dehner, Louis P; Gru, Alejandro A
This overview of mesenchymal tumors presenting in the skin and/or subcutis in children brings together the range of neoplasms and hamartomas which are seen in this age-group. It is not surprising from the perspective of the pediatric or general surgical pathologist that vascular anomalies, including true neoplasms and vascular malformations, are the common phenotypic category. Since there is considerable morphologic overlap among these lesions, clinicopathologic correlation may be more important than for many of the other mesenchymal tumors. The skin and subcutis are the most common sites of clinical presentation for the infantile myofibroma which is the most common of fibrous mesenchymal tumors in children. Several of the other mesenchymal tumors are more common adults-like dermatofibrosarcoma protuberans, but nonetheless have an important presence in children, even as a congenital neoplasm. A lipomatous tumor in a young child should be considered as a possible manifestation of an overgrowth syndrome.